Perancangan Komunikasi Visual Pengenalan Tari Pegi Mantang Kabupaten Banyuasin - Pransiska, Vira; Mubarat, Husni (Besaung : Jurnal Seni Desain dan Budaya, 2024)
Banyuasin Regency has a valuable cultural heritage in the form of the pegi mantang dance, but the younger generation lacks knowledge and interest in learning about local arts. This design aims to design a visual communication medium for introducing the pegi mantang dance to the younger generation in Banyuasin Regency. The design method used is design thinking which includes empathy, define, ideate, prototype, test. The results of this design are divided into three, including the main media in the form of cinematic videos, supporting media in the form of books, tote bag tumblers, T-Shirts, acrylic LED lights, bag hangers, and premedia in the form of posters. It is hoped that the media introducing pegi mantang dance will contribute to introducing traditional arts and overcoming the lack of awareness of the younger generation. Through an innovative visual communication approach, the younger generation can better understand, appreciate and be involved in preserving local culture. Keywords : Pegi Mantang Dance, Art, Traditional, Banyuasin